Transformasi Pemikiran Manajemen Dakwah : Dari Paradigma Tradisional ke Era Digital - kahfi, al (Journal of Da'wah, 2025)
Da'wah management is a continuously evolving discipline in response to changing times and the challenges of spreading Islamic teachings. This study aims to analyze the development of da'wah management thought, particularly in its theoretical and practical aspects across various sectors such as da'wah institutions, Islamic finance, digital da'wah, and the organization of Hajj and Umrah. This research employs a qualitative approach based on literature review and conceptual analysis. The findings indicate that da'wah management has transformed from traditional methods to more modern systems, adopting strategic management principles, digitalization, and synergy with Islamic economics. The implementation of good governance in da'wah institutions is essential to enhance transparency, accountability, and program effectiveness. Additionally, digital da'wah continues to expand through the utilization of social media and information technology for disseminating Islamic messages. This study recommends strengthening academic research, optimizing technology in da'wah, and integrating Islamic economics to ensure the sustainability of da'wah missions in the future.